Liturgical texts relating to Council of Ephesus (12 Tût) - Yūsuf, Yūḥannā Nasīm (Collectanea Christiana orientalia, 2020)
A good number of studies appear in the field of Church History dealing with the council of Ephesus considered as the third ecumenical council. In this paper, we will study the date of this council that occurs in the liturgical books. We will provide the reader with the relating liturgical texts.